Comparative Socio-Economic and Personal Characteristics of Specialized Dairy Farms of North and South Gujarat Regions - Gadhavi, GN; Rathva, AL (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
A study was carried out to compare the socio-economic and personal characteristics of commercial dairy farms/owners of north and south Gujarat. The data were collected from specialized dairy farms, each from the north and south Gujarat. Ten specialized dairy farms with a herd size of more than 40heads were selected randomly from Sabarkantha and Banaskantha districts as a sample of north Gujarat agro-climatic region and 10 farms were selected from Surat, Bharuch and Navsari districts as a sample from south Gujarat agro-climatic zone. The data were collected from dairy farm owners by administering the questionnaire. The results showed that the majority (60%) of dairy farms had livestock along with agriculture as main source of income, whereas 40% respondents had only livestock enterprise as a main source of income. Only 15% of dairy farms had other non-agricultural activities or business together with livestock. The percentage of dairy farms that had other business together with livestock was slightly higher in south region. The study revealed that majority of the respondents (55%) were of the middle age group, 40% were graduates, and 75% had experience in dairy farming for 5-10 years. Regarding the benefits of subsidy, most of the respondents availed subsidy for various farm-related purposes. About 80% of the dairy farms had taken subsidy for livestock in the north region compared to only 30% of the dairy farms in south Gujarat.